SOSIALISASI PENGGUNAAN KEKUATAN BERSENJATA/MILITER (USE OF FORCE) DALAM HUKUM INTERNASIONAL DI KOTA KUPANG - Bunga, Gerald A.; Tukan, Elisabeth Nirmalasari Bota (Universitas Mataram, 2024)
In international relations, friction or tension often arises in various fields, leading to potential conflicts between nations. When conflicts arise, the conflicting states may choose methods to resolve the dispute peacefully, or they may resort to settling the dispute through the use of force when peaceful dispute resolution methods prove inadequate. One example is the ongoing armed conflict between Russia and Ukraine, which has garnered global attention, including that of the residents of Kupang City. Therefore, the Faculty of Law has chosen to conduct a public awareness campaign on the use of force in international law for the residents of Kupang City. This awareness campaign is carried out through radio broadcasts on Programa 1 Radio Republik Indonesia to reach a broader audience in Kupang. The findings of this outreach indicate that the use of force in international relations is generally discouraged. However, when unavoidable, the use of force must adhere to the provisions of international law, whether outlined in the UN Charter or within international humanitarian law.